Failure of knee arthroplasty secondary to inadequate technique in cephalomedullary nailing of a subtrochanteric hip fracture. (3rd April 2012) - Clement, Rhys Gareth Ellis; Burnett, Richard
Abstract : A case of total knee replacement loosening caused by a failed cephalomedullary nail is presented. The nail was inserted for the treatment of an unstable subtrochanteric femoral fracture. The distal locking screw of the nail subsequently fractured allowing the leg to shorten and causing the nail to displace the femoral component of the knee replacement leading to a valgus alignment and deformity of the knee. In order to revise the knee the long γ nail had to be replaced by a shorter nail to allow a femoral component with a long stem to be used. This case illustrates the importance of using shorter nails in patients with prosthetic knees.